2022
DOI: 10.1073/pnas.2114501119
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis DNA repair helicase UvrD1 is activated by redox-dependent dimerization via a 2B domain cysteine

Abstract: Mycobacterium tuberculosis (Mtb) causes tuberculosis and, during infection, is exposed to reactive oxygen species and reactive nitrogen intermediates from the host immune response that can cause DNA damage. UvrD-like proteins are involved in DNA repair and replication and belong to the SF1 family of DNA helicases that use ATP hydrolysis to catalyze DNA unwinding. In Mtb, there are two UvrD-like enzymes, where UvrD1 is most closely related to other family members. Previous studies have suggested that UvrD1 is e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 94 publications
1
16
0
Order By: Relevance
“…We have previously shown that Mtb UvrD1 forms a disulfide-bonded dimer under oxidative conditions via a 2B domain cysteine in each subunit and that the dimeric form is an active helicase [42]. The monomeric form of UvrD1 – generated either via reducing conditions or by mutation of cysteine 451 in the 2B domain to alanine – can bind and translocate on single-stranded DNA but lacks helicase activity under previously tested conditions [42]. As it has been reported that Ku stimulates UvrD1 helicase activity [43], we performed DNA unwinding experiments with WT UvrD1 under conditions where dimer formation is favored in the presence and absence of Ku.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We have previously shown that Mtb UvrD1 forms a disulfide-bonded dimer under oxidative conditions via a 2B domain cysteine in each subunit and that the dimeric form is an active helicase [42]. The monomeric form of UvrD1 – generated either via reducing conditions or by mutation of cysteine 451 in the 2B domain to alanine – can bind and translocate on single-stranded DNA but lacks helicase activity under previously tested conditions [42]. As it has been reported that Ku stimulates UvrD1 helicase activity [43], we performed DNA unwinding experiments with WT UvrD1 under conditions where dimer formation is favored in the presence and absence of Ku.…”
Section: Resultsmentioning
confidence: 99%
“…This was true under both single-round and multi-round conditions at these fast timescales (Supplementary Figure S1A) . Since the previous Ku-dependent study presented only end point measurements taken after 10 minutes, we next asked whether Ku-dependent activation occurs on longer timescales compared to the rapid unwinding exhibited by dimeric UvrD1 [42].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…4 E; Supplementary Dataset S1). As an indication of DNA damage in the arr -KO cells, there is also a slight but statistically significant increase in the expression of uvrD (MSMEG_1941; Supplementary Dataset S1), which is known to get induced upon DNA damage in E. coli and M. tuberculosis ( Siegel, 1983 ; Chadda et al., 2022 , respectively).…”
Section: Resultsmentioning
confidence: 99%